Faecal calprotectin detects subclinical bowel inflammation and may predict treatment response in spondyloarthritis. (2nd January 2018) - Østgård, RD; Deleuran, BW; Dam, MY; Hansen, IT; Jurik, AG; Glerup, H
Abstract : Objective : Intestinal inflammation is frequent in patients with spondyloarthritis (SpA). Here, we test the validity of faecal calprotectin as a marker of intestinal inflammation in SpA patients and evaluate the response of adalimumab in patients with and without intestinal lesions. Method : Patients were included on the basis of active SpA with a Bath Ankylosing Spondylitis Disease Activity Index ≥ 4. After a 4 week non-steroidal anti-inflammatory drug washout period, patients were divided into two groups based on faecal calprotectin level (> 100 mg/kg, n = 15, and < 50 mg/kg, n = 15). Adalimumab 40 mg every other week was initiated. Patients with calprotectin >100 mg/kg received an additional 40 mg of adalimumab at baseline. Patients were followed with clinical examination at weeks 12, 20, and 52; magnetic resonance imaging (MRI) at weeks 0, 20, and 52; and endoscopy at weeks 0 and 20. Results : The groups were similar with regard to clinical disease activity measures at baseline. Faecal calprotectin above 100 mg/kg accurately identified patients with intestinal inflammation. Twelve of the 15 patients with elevated calprotectin had bowel lesions, compared to only one patient in the control group. On MRI, the group with elevated calprotectin had more inflammation in the sacroiliac joints. Finally, the group with intestinal inflammation had a better clinical response to adalimumab, as evaluated by the Ankylosing Spondylitis Disease Activity Score. Conclusion : Elevated faecal calprotectin accurately identified SpA patients with bowel inflammation and more inflammation on MRI. Elevated faecal calprotectin at baseline may predict a better treatment response.